The AN EXAMINATION OF EMPLOYEE PERKS AND THEIR IMPACT ON PRODUCTIVITY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
It is essential for a firm to have good employee relations in order to succeed. Employee relations in an organisation may be maintained by tying financial rewards to each and every job and task that an employee does for the company. It is impossible for the management of a business to overlook the importance of employee benefits, which are the different non-wage compensations that are given to employees in addition to their earnings or salary. In today's competitive environment, firms of all sizes, technological capabilities, and market emphasis are struggling to keep their best employees. Workers and their employers must have a strong and positive bond to overcome these constraints. Employees should be encouraged to do their best by giving them with enticing employee incentives like as performance bonuses, Christmas bonuses, study allowances, and leave allowances, etc. in order to strengthen this good connection. A company's greatest asset is its people, and motivating and persuading them to carry out their duties is an ongoing process.